Butylidenephthalide antagonizes cromakalim-induced systolic pressure reduction in conscious normotensive rats. Issue 1 (December 2015) - Shih, Chung-Hung; Lin, Yu-Jing; Chen, Chi-Ming; Ko, Wun-Chang
Abstract Background Butylidenephthalide (Bdph), a main constituent ofLigusticum chuanxiong Hort., was reported to have selective antianginal effect without changing blood pressure in conscious rat. Recently, we have observed that Bdph antagonized cromakalim, an ATP-dependent K+ channel opener, in guinea-pig trachea. Thus, we were interested in investigating whether Bdph at the dose without changing blood pressure antagonized cromakalim-induced systolic pressure reduction in conscious rats. Methods Systolic arterial pressures of conscious rats were determined by using the indirect tail-cuff method. Results Bdph (30 mg/kg, i.p.) did not affect baseline systolic pressure in conscious normotensive and spontaneous hypertensive rats. Bdph (30 mg/kg, i.p.) also did not affect log dose–response curves of prazosin, clonidine and Bay K 8644, a Ca2+ channel activator, in normotensive rats. However, Bdph (30 mg/kg, i.p.) similar to 4-aminopyridine (4-AP, 0.4 mg/kg, i.p.), a K+ channel blocker, non-parallelly but surmountably, and partially similar to glibenclamide (GBC, 10 mg/kg, i.v.), an ATP-sensitive K+ channel blocker, surmountably but not parallelly rightward shifted the log dose-systolic pressure reduction curve of cromakalim, an ATP-sensitive K+ channel opener, in normotensive rats, respectively. Discussion The antagonistic effect of Bdph against cromakalim was similar to that of 4-AP, a K+ channel blocker of Kv1 family, and partially similar to that of GBC, an ATP-sensitive K+ channel blocker. Thus, Bdph may be a kind of K+ channel blockers, which have been reviewed to have a potential clinical use for Alzheimer disease. Indeed, Bdph has also been reported to reverse the deficits of inhibitory avoidance performance and improve memory in rats. Recently, 4-AP was reported to treat Episodic ataxia type 2 (EA2) which is a form of hereditary neurological disorder. Consistently, Bdph was recently reported to have antihyperglycemic activity in mice, since GBC is a powerful oral hypoglycemic drug. Conclusions Bdph similar to 4-AP and partially similar to GBC may block Kv 1 family and ATP-sensitive K+ channels in conscious normotensive rats.